Pemanfaatan Aplikasi Canva untuk membuat Media Bimbingan dan Konseling Bagi MGBK Kabupaten Gowa - Abdul Saman; Nur Fadilah Umar; Muhammad Ilham Bakhtiar; Akhmad Harum (Ilin Institute, 2021)
The purpose of this Community Service is to increase the understanding of BK Teachers in utilizing the Canva Application in making Guidance and Counseling Service Media in the form of Guidance Brochure media, Percentage Media for classical services, 3D Posters using video and audio services, activity flyers. The methods used are: lectures, practice, question and answer, and assistance in making media done online, and. The materials provided are Media in Counseling Services and Types of Media in Counseling Services, IT-Based Media in Counseling Services, introduction to Canva Application Media and continued Practice using Canva Application media accompanied by a PKM team Such as making brochures, counseling posters, online guidance boards, posters Multimedia services use animated audio and video, creating percentage media for classical services. The results of the PKM are (1) the results of the training 96% of participants stated that this training provided enormous benefits in guidance and counseling services and various service media were available that could be used in Guidance and Counseling activities. (2) After the training, there is an increase in the manufacture of guidance and counselling service media through the use of the Canva application. There are 41 people or 91% of participants who are very capable of using the Canva application. This shows that this training has a very big influence in making media that can be used in services